THE E-LEARNING IN FRENCH LANGUAGE AND LITERATURE DEPARTMENT OF THE UNIVERSITY OF MASCARA DURING THE COVID-19 CRISIS: QUANTITATIVE STUDY - Aouda MAZOT (Analele Universităţii din Craiova. Psihologie, Pedagogie)
This research aims to evaluate the steps, means and resources implemented by the French language and literature department at Mustapha Stambouli University, Mascara, for the “smooth” running of e-learning, during the containment imposed by the Algerian government and applied in all sectors including higher education and scientific research, following the Covid-19 pandemic. 232 students were surveyed, exploring their experiences of distance learning and their evaluation of the digital resources made available to them by the university. The results highlight the strengths and weaknesses of this type of teaching, and the shortcomings of the tools used by the administration. The respondents' answers open up new perspectives on the problem of teacher training in ICTE and on the quality of the digital resources and applications available on the University of Mascara's e-learning platform.